2022
DOI: 10.3847/1538-4357/ac3fb3
|View full text |Cite
|
Sign up to set email alerts
|

IRAM 30 m CO-line Observation toward the PeVatron Candidate G106.3+2.7: Direct Interaction between the Shock and the Molecular Cloud Remains Uncertain

Abstract: The supernova remnant (SNR) G106.3+2.7 was recently found to be one of the few potential Galactic hadronic PeVatrons. Aiming to test the solidity of the SNR’s association with the molecular clouds (MCs) that are thought to be responsible for hadronic interaction, we performed a new CO observation with the IRAM 30 m telescope toward its “belly” region, which is coincident with the centroid of the γ-ray emission. There is a filament structure in the local standard of rest velocity interval −8 to −5 km s−1 that n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…On the other hand, the molecular clouds found in the complex seem to have a different spatial distribution, with the location coincident with the tail region in our line of sight based on CO observations [4]. However, it is still uncertain whether the molecular clouds are directly disturbed by the SNR shocks [7], but they are expected to be nearby and thus can still be illuminated by the protons that escaped from the SNR [8,9].…”
Section: Introductionmentioning
confidence: 66%
“…On the other hand, the molecular clouds found in the complex seem to have a different spatial distribution, with the location coincident with the tail region in our line of sight based on CO observations [4]. However, it is still uncertain whether the molecular clouds are directly disturbed by the SNR shocks [7], but they are expected to be nearby and thus can still be illuminated by the protons that escaped from the SNR [8,9].…”
Section: Introductionmentioning
confidence: 66%
“…Emission of gamma rays with energies higher than 100 TeV was detected by HAWC (Albert et al 2020), Tibet AS γ (Amenomori et al 2021), and LHAASO (Cao et al 2021); the ultrahigh-energy (UHE) source is coincident with the VER-ITAS and Fermi-LAT sources in the tail region as well as with PSR J2229+6114 (Albert et al 2020). The UHE detection identified the Boomerang region as a PeVatron candidate, but its origin is still debated between the leptonic and hadronic cases associated with the Boomerang PWN and the SNR interaction with molecular clouds, respectively (Bao & Chen 2021;Fujita et al 2021;Ge et al 2021;Breuhaus et al 2022;Liu et al 2022). Various high-energy emission centroids/extents are depicted over the map of 1420 MHz radio temperature brightness of SNR G106.3+2.7 in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, some of the LHAASO PeV detection regions could be correlated with SNRs, keeping open the possibility of having PeV emissions from this kind of source, even after their 100 yrs [52][53][54][55]. Several studies are in progress to establish a "look up table" of parameters useful for future instruments to distinguish which SNRs are hadronic [56,57].…”
Section: Status Of the Field After The Lhaaso Resultsmentioning
confidence: 99%
“…Recently, a 12-year Fermi-LAT GeV analysis of the region showed that at the highest energies (10-500 Gev), only the tail is emitting γ-ray (see Figure 16, top left) and a hadronic model from the SNR/MC interaction can explain the entire HE/VHE/UHE spectrum [54]. Recently, the MAGIC collaboration resolved the VHE/UHE emission and detected E > 10 TeV only from the tail region [52,200], leaning towards a hadronic explanation of the γ-ray emission [199,200], and linked to the SNR/MC interaction (or MC illumination form CRs escaping from the SNR [53]). The hadronic model used by the MAGIC collaboration also took into account the GeV Fermi-LAT data points from the tail region from [201] (consistent with the more recent results from [54]) (see Figure 16, top right).…”
Section: Lhaaso J2226+6057mentioning
confidence: 99%